FINANCING OF HIGHER EDUCATIONAL INSTITUTIONS WITH BUDGETARY FUNDS IN UZBEKISTAN - Xaydarova Farida Muxtarovna (Galaxy International Interdisciplinary Research Journal, 2023)
Financing of higher educational institutions with budgetary funds in Uzbekistan is a crucial issue that needs to be addressed. Higher education plays a significant role in the development of any country, and Uzbekistan is not an exception. The government of Uzbekistan has always been committed to providing quality education to its citizens, but the financing of higher educational institutions has been a challenge for the country. In this article, we will discuss the current state of financing of higher educational institutions with budgetary funds in Uzbekistan, its challenges, and possible solutions.